Symbiosal® and lowering of blood pressure and reduced risk of hypertension: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (EFSA NDA Panel); Turck D; Bresson J-L; Burlingame B; Dean T; Fairweather-Tait S; Heinonen M; Hirsch-Ernst KI; Mangelsdorf I; McArdle HJ; Naska A; Neuhäuser-Berthold M; et al. (John Wiley and Sons Ltd on behalf of European Food Safety Authority, 2018)
Following an application from Han-Biotech GmbH, submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of Germany, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Symbiosal®, lowering of blood pressure and reduced risk of hypertension. The Panel considers that the food, Symbiosal®, which is the subject of the health claim, and the food, table salt, which Symbiosal® should replace, are sufficiently characterised. Lowering of blood pressure is a beneficial physiological effect. Increased blood pressure is a risk factor for hypertension. In weighing the evidence, the Panel took into account that one human study with some methodological limitations showed an effect of Symbiosal® on blood pressure in the context of a self-selected diet with a maximum of 3 g/day added salt. The Panel also took into account that no other human studies in which these results have been replicated were provided, that the animal studies did not support the results of the human study, that no evidence was provided in support of a mechanism by which Symbiosal® could induce a decrease in blood pressure upon oral consumption as compared to table salt in vivo in humans, and the low biological plausibility of the effect observed in the human intervention study. The Panel concludes that a cause and effect relationship has not been established between the consumption of Symbiosal® and lowering of blood pressure.
Keywords: Symbiosal((R)); chitosan; blood pressure; hypertension; health claim